Analisis Faktor – Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa di Kabupaten Lombok Tengah - Luthfiani, Baiq Mira; Asmony, Thatok; Herwanti, Rr Titiek (E-Jurnal Akuntansi, 2020)
Accountability of village fund management is the responsibility of the village government to the community related to village fund management. This study aims to obtain empirical evidence of the influence of the competence of village officials, the application of the social security system, the tax treasurer compliance of the village treasury and community participation in the accountability of village fund management. The method in this research is descriptive quantitative with data analysis techniques using multiple linear regression test. The study was conducted in 127 in 12 districts of Central Lombok Regency. The samples in this study were 88 people who were determined using the purposive sampling method. Data collected by questionnaire method. The results showed the competence of village officials and community participation did not affect the accountability of village fund management, while the application of the siskeudes and tax treasury compliance of the village treasurer had a positive effect on the accountability of village fund management. Keywords: Accountability; Device Competency; Siskeudes Application; Tax Compliance; Society Participation.